A Resilient and Reusable Ion-Tagged Cu(II) Catalyst for the Microwave-Assisted Synthesis of 2-(N-Arylamino)benzothiazoles - Ahmad, Md Gulzar; Balamurali, M M; Chanda, Kaushik (Synlett, 2024)
A simple, quick, and cost-effective protocol is presented herein for the sustainable synthesis of 2-(N-arylamino)benzothiazoles from 2-haloanilines and arylisothiocyanates by using an ionic liquid supported heterogeneous Cu(II) catalyst derived from N-methylimidazole. Compared to the use of homogeneous catalysts and additives, which require long reaction times and high reaction temperatures, this methodology has a broad substrate scope and proceeds in short reaction times to afford compounds in excellent yields under microwave irradiation. In addition, the catalyst can be extracted easily and is recyclable up to five times with no significant loss in catalytic activity.
Keywords: 2-aminobenzothiazoles; ionic liquids; microwave irradiation; Cu(II) catalysts; sustainable synthesis